REKONSTRUKSI SISTEM JAMINAN SOSIAL NASIONAL BIDANG KESEHATAN BERBASIS NILAI KESEJAHTERAAN - Urip Santoso (UNISSULA, 2014)
Optimalized national development can be achieved if the development of public health can be realized, as a form of implementation of the development is manifested in the form of government in providing welfare guarantees health care for all the people of Indonesia. The establishment of social security health agencies as providers of health insurance is expected to answer and respond to the challenges of health development in the present and in the future. Research methods used are legal social research data sources consist of primary data andsecondary data, research approaches have been to see the extent to which the effectiveness of the law in the welfare of society, especially in the protection of health insurance. Based on the research results can be known, that the legal construction of the national social security system in the health sector positive law currently regulated in Law Number 40 of 2004 on the national social security system, while for health care procedures in the administration of health services stipulated in Presidential Decree No. 111 2013 on the national health insurance, some things that need to be reconstructed, namely the reconstruction of the legal substance of Article 39 Presidential Decree No. 111 of 2013 on national health insurance, the reconstruction of the legal structure of the national social security system on a generalization of a national health insurance program, the reconstruction of the legal culture of the national social security system Sector Value-Based Health Welfare.